Food52 mighty salads : 60 new ways to turn salad into dinner-and make-ahead lunches, too - Hesser, Amanda; Stubbs, Merrill (Ten Speed Press, 2017)
A collection of recipes for hearty salads features such options as charred brocolli and lentil salad, spring vegetable panzanella, grilled lobster salad with lemon-thyme butter, and curried chicken, grape and cheddar salad.